Pedagogical Approaches to Teacher Professional Development in Contexts of Mass Displacement: An Agenda for Research and Practice - Tejendra Pherali; Min Layi Chan; Wirachan Charoensukaran; Elaine Chase; Eileen Kennedy; Greg Tyrosvoutis; Gabi Witthaus; Diana Laurillard (Journal of Interactive Media in Education)
Educational providers frequently respond to learning disruptions encountered by refugees, internally displaced persons, and migrant communities through online platforms. Learning modules in these digital spaces are often remotely designed, prescriptive and lack full appreciation of challenging circumstances faced by teachers and learners. To sustain meaningful learning in conflict and crisis, the crucial role of teachers cannot be overestimated. Drawing on research into teacher professional development (TPD) through Co-designed Massive Open Online Collaborations (CoMOOCs) in Lebanon, which have global reach, we critique decontextualised and rigid approaches to TPD and highlight the importance of enabling local solutions through dialogue and collaboration with refugee educators. We argue for working from local needs, trialling and harnessing local solutions, and sharing these methods and outcomes globally so that others can consider their relevance and adapt them to their own contexts. We illustrate this approach through presenting our current work with teachers of refugees and migrants from Myanmar now in Thailand, highlighting the research agenda and potential of CoMOOCs to support TPD in this context by: 1) supporting teachers to collaborate with peers in similar contexts; 2) understanding how scholars in the Global North can help facilitate South-South collaborations through global online learning infrastructures; 3) addressing linguistic barriers for teachers learning in online environments; and 4) planning teacher certification to recognise their pedagogical knowledge and skills. The paper describes our “Theory of Change” for widening access to quality tertiary education through TPD in contexts of mass displacement, thereby fostering hope, empowerment, and resilience in the face of adversity.